Hepatoprotective Effects of Silybum marianum (Silymarin) and Glycyrrhiza glabra (Glycyrrhizin) in Combination: A Possible Synergy. (25th March 2014) - Rasool, Mahmood; Iqbal, Javed; Malik, Arif; Ramzan, Hafiza Sobia; Qureshi, Muhammad Saeed; Asif, Muhammad; Qazi, Mahmood Husain; Kamal, Mohammad Amjad; Chaudhary, Adeel Gulzar Ahmed; Al-Qahtani, Mohammed Hussain; Gan, Siew Hua; Karim, Sajjad
Abstract : Oxidative stress, lipid peroxidation, and transaminase reactions are some of the mechanisms that can lead to liver dysfunction. A time-dependent study was designed to evaluate the ability of silymarin (SLN) and glycyrrhizin (GLN) in different dosage regimens to lessen oxidative stress in the rats with hepatic injury caused by the hepatotoxin carbon tetrachloride. Wistar male albino rats (n = 60) were randomly assigned to six groups. Group A served as a positive control while groups B, C, D, E, and F received a dose of CCl4 (50% solution of CCl4 in liquid paraffin, 2 mL/kg, intraperitoneally) twice a week to induce hepatic injury. Additionally, the animals received SLN and GLN in different doses for a period of six weeks. CCl4 was found to induce hepatic injury by significantly increasing serum alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and thiobarbituric acid reactive substances while decreasing total protein and the activities of reduced glutathione, superoxide dismutase, and catalase. Treatment with various doses of SLN and GLN significantly reduced ALT, AST, ALP, and TBARS levels and increased GSH, SOD, and CAT levels. Our findings indicated that SLN and GLN have hepatoprotective effects against oxidative stress of the liver.